Digitalization of Processes of Small and Average Business - A. V. Polyanin; Yu. P. Soboleva; V. V. Tarnovskiy (Управленческое консультирование)
The role of small and medium-sized enterprises in the economic life of society cannot be overestimated: it contributes to economic growth in the country, increases the level of employment of the population, forms healthy competition, promotes the development of innovation activities and solves many social problems. In this regard, State support for entrepreneurship is essential in order to create an enabling environment for its further development. To date, a national project on the formation of support mechanisms for small and medium-sized enterprises has been adopted and is being implemented. The relevant national project is implemented within the framework of five federal projects aimed at improving the conditions of entrepreneurship, access of business entities to financial resources, acceleration of business entities, popularization of entrepreneurship, and development of rural cooperation. At the same time, in the context of digital globalization, the effective implementation of these directions is impossible without the introduction of information technologies into the activities of the business entities themselves. Research on the introduction of information technologies into business structures is not systematic and reveals certain aspects of this issue. The relevance of the study is due to the fact that within the framework of the national projects approved in our country, no mechanism has been developed to form a business model that ensures the effective introduction of such technologies into the activities of small and medium-sized businesses. Most scientific works of this topic reveal issues of implementation of specific information technologies by business entities. Therefore, the formation of a generalized model of effective introduction of IT-technologies in the activities of small and medium-sized enterprises is a pressing task that contributes to the achievement of the tasks set for national projects.The purpose of this study is to develop methodological and practical recommendations to increase the efficiency of Russian small and medium-sized enterprises on the basis of the implementation of the concept of digitalization of business. The study was aimed at national projects “Small and medium-sized entrepreneurship and support for individual entrepreneurial initiative” and “Digital economy of the Russian Federation,” interim results of their implementation. The subject of the study is the system of support for the development of Russian small and medium-sized enterprises.The scientific novelty of this study consists in the development of an algorithm for the transition of small and medium-sized enterprises to digitalization of business processes, in the systematization of business entities by the level of introduction of digital technologies into the activities, as well as in the grouping of the main directions of digitization of business entities.